Der Verein der Schriftstellerinnen und Künstlerinnen in Wien - Baumgartner, Marianne (Böhlau, 2021)
On the evening of April 1, 1885, a group of women who were active in artistic fields founded in Vienna the »Verein der Schriftstellerinnen und Künstlerinnen in Wien« (the »Association of Female Authors and Artists in Vienna« or VSKW). Their goal was to establish a social network for themselves that, aside from providing financial security in the event of need, illness or old age, could also offer a forum for promotion and support. Based upon reports pertaining to the Association and on documents about or authored by its members from their personal archives (e.g. diaries and unpublished letters), the book focuses on the efforts of the members to achieve unity despite their extremely diverse social and artistic backgrounds, on their searches for internal and external orientation, on their successes, but also on their hindrances and failures.